Una prospectiva de la formación en la profesión contable (2017)
The author makes a compilation of main topics of discussion and reflection in the field of accounting education, taking as reference the journals specialized in the subject that originate in the Anglo-Saxon academic world, establishing a comparison between the themes and trends in the publication in Colombia and the United States and England. The author concludes that although the subjects in which accounting education is researched are not so different, it is clear that in the Anglo-Saxon world, the coordinated structure of work, the availability of methodological and theoretical tools and the circulation of knowledge, are different and configure a field of work very different from the one that develops in our context.